2012
DOI: 10.1111/j.1468-3083.2011.04441.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on serum 8‐hydroxy guanosine (8‐OHdG) as reliable biomarker for psoriasis

Abstract: Serum 8-OHdG levels could be used as good biomarker for the early diagnosis of psoriasis and its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
1
29
1
Order By: Relevance
“…Decreased expression of CAT, SOD, and GPx was observed [259261]. Moreover, mitochondrial damage could be inferred by release of mitochondrial cytochrome c and by upregulated CYP4F8 mRNA [262, 263].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Decreased expression of CAT, SOD, and GPx was observed [259261]. Moreover, mitochondrial damage could be inferred by release of mitochondrial cytochrome c and by upregulated CYP4F8 mRNA [262, 263].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Recent evidence suggests that the redox imbalance found in blood and skin of the patients plays an important role in the pathogenesis of psoriasis. 3 Indeed, numerous studies revealed significantly increased levels of oxidative stress markers such as malondialdehyde (MDA), nitric oxide end products, [3][4][5][6] and 8-OHdG (8-hydroxydeoxyguanosine) 7 in the plasma of psoriatic patients. Likewise, decreased total antioxidant capacity (TAC), vitamin A and E levels, and decreased activity of the main antioxidant enzymes (such as erythrocyte and serum superoxide dismutase and catalase) were also found in the plasma of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, decreased total antioxidant capacity (TAC), vitamin A and E levels, and decreased activity of the main antioxidant enzymes (such as erythrocyte and serum superoxide dismutase and catalase) were also found in the plasma of these patients. [3][4][5][6]8 Moreover, the 'severity' of plasma redox imbalance was found to be strongly correlated with the Psoriasis Area and Severity Index (PASI), [4][5][6][7][8] which in turn correlates with the level of inflammatory cytokines. 8 The central role of TNF-α in the pathogenesis of psoriasis has been demonstrated by the clinical efficacy of TNF-α antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous biomarker investigations were performed in psoriasis. Serum 8‐hydroxy‐2‐deoxyguanosine (8‐OHdG) was proposed as a biomarker for the early diagnosis, and serum human beta‐defensin (HBD‐2), but not TNF‐like ligand 1A (TL1A), was reported to be a useful marker for disease activity . Plasma levels of transforming growth factor (TGF)‐beta1, tissue inhibitors of metalloproteinases (TIMP)‐1, matrix metalloproteinase (MMP)‐1 and interleukin (IL)‐18 were found to be associated with psoriasis severity and treatment efficacy .…”
Section: Biomarkers and Personalized Medicine In The Dermatological Pmentioning
confidence: 99%